Biochemical Roles of Eukaryotic Cell Surface Macromolecules - Chakrabarti, Abhijit (Springer, 2015)
Consists of critical reviews and original research papers from the 2014 International Symposium on the "Biochemical Role of Eukaryotic Cell Surface Macromolecules". Topics covered include: · neurochemical and biochemical analysis of cell surface glycoconjugates · membrane skeletal organization · GPCRs and other receptors · biophysical approaches to study membrane interactions · glycoconjugate metabolism · dysregulation · molecular mechanisms involved in cell-cell and cell-matrix interaction · glycans in infectious and neurological diseases · cancer and glycosyltransferases as drug targets.